2021
DOI: 10.1111/ctr.14384
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of living kidney donor enhanced recovery after surgery

Abstract: Enhanced recovery after surgery (ERAS) reduces complications and shortens hospital stay without increasing readmission or mortality. However, its role in living donor nephrectomy (LDN) has not yet been defined. Medline, Embase, CINAHL, PsycINFO, and Cochrane Central were searched prior to 08/01/21 for all randomized controlled and cohort studies comparing ERAS to standard of care in LDN. The study was registered on PROSPERO (CRD: CRD42019141706). One thousand, three hundred seventy-seven patients were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
3
0
1
Order By: Relevance
“…A systematic review of ERAS protocols for living kidney donors presented a limited number of randomized controlled trials; most were retrospective cohort studies. 15 Although the positive benefits of ERAS were suggested in the review, only a few studies have investigated the effectiveness of the TAP block. One retrospective single-center study discovered that bupivacaine or liposomal bupivacaine TAP block reduced the postoperative opioid requirement after laparoscopic donor nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of ERAS protocols for living kidney donors presented a limited number of randomized controlled trials; most were retrospective cohort studies. 15 Although the positive benefits of ERAS were suggested in the review, only a few studies have investigated the effectiveness of the TAP block. One retrospective single-center study discovered that bupivacaine or liposomal bupivacaine TAP block reduced the postoperative opioid requirement after laparoscopic donor nephrectomy.…”
Section: Discussionmentioning
confidence: 99%
“… 14 A systematic review of living donor nephrectomy showed that with laparoscopic procedures duration of stay was significantly reduced by 0.98 d in the ERAS group. Opiate requirement was reduced by 32.4 mg. 15 A meta-analysis showed that ERAS protocols result in reduced perioperative morbidity, shorter length of hospital stay and improved quality of life after living donor nephrectomy. 16 A study reviewed ERAS in kidney transplant recipients and was targeting a discharge home within 5 d of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Отмечен достоверно менее выраженный послеоперационный болевой синдром и риски развития послеоперационной тошноты и рвоты без увеличения риска реадмисии. Аналогичные выводы получены в исследованиях, посвященных сравнению стандартного лечебного подхода и протокола ускоренного выздоровления при резекции почки [9] и при донорской нефрэктомии [17]. При этом размер удаляемого органа не коррелирует напрямую с общим суммарным размером доступа и объемом операционной травмы при применении современного инструментария, шейвера или фрагментации удаляемой почки [18].…”
Section: Discussionunclassified